Genetic Landscape of SH3TC2 variants in Russian patients with Charcot–Marie–Tooth disease - Shchagina, Olga; Murtazina, Aysylu; Chausova, Polina; Orlova, Mariya; Dadali, Elena; Kurbatov, Sergei; Kutsev, Sergey; Polyakov, Aleksander (Frontiers in Genetics, 2024)
Introduction: Charcot–Marie–Tooth disease type 4C (CMT4C) OMIM#601596 stands out as one of the most prevalent forms of recessive motor sensory neuropathy worldwide. This disorder results from biallelic pathogenic variants in the SH3TC2 gene. Methods: Within a cohort comprising 700 unrelated Russian patients diagnosed with Charcot–Marie–Tooth disease, we conducted a gene panel analysis encompassing 21 genes associated with hereditary neuropathies. Among the cohort, 394 individuals exhibited demyelinating motor and sensory neuropathy. Results and discussion: Notably, 10 cases of CMT4C were identified within this cohort. The prevalence of CMT4C among Russian demyelinating CMT patients lacking the PMP22 duplication is estimated at 2.5%, significantly differing from observations in European populations. In total, 4 novel and 9 previously reported variants in the SH3TC2 gene were identified. No accumulation of a major variant was detected. Three previously reported variants, c.2860C>T p. (Arg954*), p. (Arg658Cys) and c.279G>A p. (Lys93Lys), recurrently detected in unrelated families. Nucleotide alteration p. (Arg954*) is present in most of our patients (30%).